2022
DOI: 10.1364/ol.464148
|View full text |Cite
|
Sign up to set email alerts
|

Multi-channel parallel ultrasound detection based on a photothermal tunable fiber optic sensor array

Abstract: A multi-channel parallel ultrasound detection system based on a photothermal tunable fiber optic sensor array is proposed. The resonant wavelength of the ultrasound sensor has a quadratic relationship with the power of a 980-nm heating laser. The maximum tuning range is larger than 15 nm. Through photothermal tuning, the inconsistent operating wavelengths of the Fabry–Perot (FP) sensor array can be solved, and then a multiplexing capacity of up to 53 can be theoretically realized, which could greatly reduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, the F-P cavities in different channels may have different resonance wavelengths, which poses a challenge for optical readout. To address this issue, Yang et al demonstrated a photothermal tunable fiber optic ultrasound sensor array, where the resonant wavelength of each cavity can be controlled by a laser 69 . Furthermore, Ma et al proposed a 4 × 16 fiber-optic array based on F-P cavities, which enabled parallel sensing for imaging with a volume rate of 10 Hz 70 .…”
Section: Optical Microcavity Ultrasound Sensorsmentioning
confidence: 99%
“…However, the F-P cavities in different channels may have different resonance wavelengths, which poses a challenge for optical readout. To address this issue, Yang et al demonstrated a photothermal tunable fiber optic ultrasound sensor array, where the resonant wavelength of each cavity can be controlled by a laser 69 . Furthermore, Ma et al proposed a 4 × 16 fiber-optic array based on F-P cavities, which enabled parallel sensing for imaging with a volume rate of 10 Hz 70 .…”
Section: Optical Microcavity Ultrasound Sensorsmentioning
confidence: 99%
“…Among them, fiber optic resonant structures for ultrasound sensors have strong competivity [12] , [16] , [17] , [18] , due to the outstanding performances of high sensitivity and smaller size. In theory, the sensor structures including polymer-membrane based Fabry-Perot interferometers (FPI) [12] , [19] , fiber gratings [15] , [20] and micro-ring resonators [17] have extremely high sensitivity with a very small footprint owing to the long interaction length. The spectral sideband filter technique is commonly used to achieve signal demodulation for ultrasound detection [21] , [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%